Characteristics of paediatric burn injuries seen in the tertiary emergency centre, South Africa - Ntsovelo Mugwena; Rule Human; Maria M. Geyser (South African Family Practice)
Background: Burn injuries cause significant morbidity and mortality, with prevalence in developing countries such as South Africa. This study aimed to determine the characteristics and referral patterns of burn injuries.